Application of Taguchi method to optimise the process parameters in additive manufacturing - Maidin, Shajahan; Fadani, Irdawati (Penerbit UTeM Press, 2024)
Fused deposition modelling is becoming ubiquitous today because it is commonly used for prototyping and product applications. However, FDM still needs to catch up regarding product quality. Surface quality plays a significant role in producing precise parts, and it is one of the limiting aspects of additive manufacturing technology. Therefore, this book introduces and shows the feasibility and the process of using the Taguchi method to optimise four process parameters, namely layer height, flow rate, printing temperature, and printing speed, to improve the surface roughness. Taguchi 3 and L9 orthogonal array were used to design the experiment. Samples of models of the same size were fabricated in an FDM printer using acrylonitrile butadiene styrene material and were examined to see the structural differences. The S/N ratio and means analysis were used to find the optimum process parameter for surface roughness. The results indicated that flow rate was the most influential process parameter towards good surface roughness, followed by layer height, printing temperature, and print speed. The surface roughness of printed parts was rougher with the increase in the flow rate levels. The flow rate is responsible for the unevenly aligned section of the deposited filament. It was discovered that the optimal parameter levels for surface roughness by the CR-10S Pro FDM machine are 0.1 mm of layer height, 90% of flow rate, 230°C of printing temperature, and 35 mm/s of print speed. Thus, the Taguchi method proved valuable for optimising parameters to improve the surface roughness of printed parts.